Preparing for Practice: Clinical Legal Education Through the Lens of Legal Education Discourse - Jackson Walkden-Brown; Lindsey Stevenson-Graf (Australian Journal of Clinical Education)
Australian legal educators have been singing the praises of clinical legal education loud and clear in recent years. Moreover, a significant percentage of Australian law schools have introduced diverse clinical education programs. While it is widely accepted that clinical subjects are a welcome addition to the modern law student experience, it is contended that there are varied perspectives on the appropriate function and design of clinical subjects and programs. The purpose of this paper is to conceptualise these diverse perspectives by examining clinical legal education through the lens of legal education discourse. Legal education is characterised by distinct and competing discourses with respect to the nature of law teaching, including doctrinalism, vocationalism, corporatism, liberalism, radicalism and educationalism. The first part of the paper provides an overview of Foucauldian discourse theory and a description of each legal education discourse. The second part of the paper provides an analysis of clinical legal education in the context of each discourse, illustrating the distinctive features of CLE that are aligned and misaligned with the fundamental tenets of each discourse. An introduction to legal education discourse serves to provide law teachers with a sense of objective clarity regarding the competing perspectives that characterise typical law school debates on matters of pedagogy, such as clinical legal education.